(untitled) (Journal of Oriental Studies, 2019)
In connection with the adoption of the Legislation of the Republic of Kazakhstan, providing for the principle of equal rights to education for persons with disabilities there was a question about the preparation of teachers-psychologists for work in inclusive education. Inclusive education exists in Eu- rope and America for many decades, in spite of a certain experience in the implementation of inclusive education in the General education system the introduction of inclusive education has not been studied thoroughly. As inclusive education is about equal rights of children with disabilities to education in sec- ondary schools with normally developed children and to have access to all areas of social life, to have the opportunity to develop their abilities, talents and most importantly, communicate with their peers with normal development health. As well as inclusive education implies education for children with special needs in accordance with the place of residence, receipt of various social services at the place of residence. But to fully provide educational facilities need trained professionals. This article describes a number of views of scientists on the preparation of teachers – psychologists, provided competence- based approach, which gives a clear idea about the impact and importance of a number of competence for the training of educational psychologist. The structure of the competence approach will allow future teachers-psychologists in their future work with children with special needs. Key words: inclusive education, children with special needs, competence-based approach.